The Growth Effects of Education in Australia. - Antonio Paradiso; Saten Kumar; B. Bhaskara Rao (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2011)
In this paper we estimate the growth effects of human capital with country-specific time series data for Australia. Previous empirical studies, based on international data, have been inconclusive, in terms of the extent of the contribution of human capital to growth. We extend the Solow (1956) growth model by using educational attainment as a measure of human capital, as developed by Barro and Lee (2010). The extended Solow (1956) model performs well after allowing for the presence of structural changes. Our results, based on alternative time series methods, show that educational attainment has a small and significant permanent effect on the growth rate of per worker output in Australia. Alternative measures of human capital are also utilized to ensure robustness of results.
Keywords: C22; O56; O40; 330; Steady State Growth Rates; Economic Growth; Education; Australia